2023
DOI: 10.3389/fnmol.2023.1091323
|View full text |Cite
|
Sign up to set email alerts
|

The TSC2 c.2742+5G>A variant causes variable splicing changes and clinical manifestations in a family with tuberous sclerosis complex

Abstract: BackgroundTuberous sclerosis complex (TSC) is a genetic, variably expressed, multisystem disease characterized by benign tumors. It is caused by pathogenic variants of the TSC complex subunit 1 gene (TSC1) and the TSC complex subunit 2 gene (TSC2). Genetic testing allows for early diagnosis, genetic counseling, and improved outcomes, but it did not identify a pathogenic variant in up to 25% of all TSC patients. This study aimed to identify the disease-causing variant in a Han-Chinese family with TSC.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our previous research using minigene assay identified a novel TSC2 c.336_336 + 15delGGTAAGGCCCAGGGG variant in a TSC patient (Liu et al, 2022). Fan et al identified a TSC2 c.2742 + 5G>A variant using the same method (Fan et al, 2023). Similarly, our study conducted a minigene assay to confirm the pathogenicity of the variant.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our previous research using minigene assay identified a novel TSC2 c.336_336 + 15delGGTAAGGCCCAGGGG variant in a TSC patient (Liu et al, 2022). Fan et al identified a TSC2 c.2742 + 5G>A variant using the same method (Fan et al, 2023). Similarly, our study conducted a minigene assay to confirm the pathogenicity of the variant.…”
Section: Discussionmentioning
confidence: 68%
“…Fan et al. identified a TSC2 c.2742 + 5G>A variant using the same method (Fan et al., 2023 ). Similarly, our study conducted a minigene assay to confirm the pathogenicity of the variant.…”
Section: Discussionmentioning
confidence: 99%